A small group of sulfated benzofurans induces steady-state submaximal inhibition of thrombin. Issue 6 (1st April 2018) - Afosah, Daniel K.; Verespy, Stephen; Al-Horani, Rami A.; Boothello, Rio S.; Karuturi, Rajesh; Desai, Umesh R.
Graphical abstract: Abstract: Despite the development of promising direct oral anticoagulants, which are all orthosteric inhibitors, a sizable number of patients suffer from bleeding complications. We have hypothesized that allosterism based on the heparin-binding exosites presents a major opportunity to induce sub-maximal inhibition of coagulation proteases, thereby avoiding/reducing bleeding risk. We present the design of a group of sulfated benzofuran dimers that display heparin-binding site-dependent partial allosteric inhibition of thrombin against fibrinogen (ΔY = 55–75%), the first time that a small molecule (MW  < 800) has been found to thwart macromolecular cleavage by a monomeric protease in a controlled manner. The work leads to the promising concept that it should be possible to develop allosteric inhibitors that reduce clotting, but do not completely eliminate it, thereby avoiding major bleeding complications that beset anticoagulants today.